A validity study of the Philippine Science High School nonverbal test of academic aptitude - Dacanay, Digna Carino 1946- (1976)
The purpose of this validity study was to assess at this stage of its development, to what extent the nonverbal test of academic aptitude serves the purposes for which it was included in the Philippine Science High School (PSHS) entrance examinations. It examined this in terms of construct and criterion related validity indices.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Philippine Science High School -- Entrance requirements; Non-verbal mental test; Scholastic aptitude test